Inside major East Asian library collections in North America. volume 1 - Lo, Patrick; Anghelescu, Hermina; Allard, Bradley (Bingley, U.K. : Emerald Publishing Limited, 2022)
As a branch of International and Area Studies Librarianship (IASL), East Asian Librarianship has become increasingly important in an age of globalization as scholars engage in interdisciplinary research and study. Volume 1 of Inside Major East Asian Library Collections in North America presents an extensive collection of interviews that give key insights into Japanese and Korean librarianship. East Asian Studies librarianship requires a variety of technical skills, combining deep subject background with knowledge of library processes/workflows, an awareness of research trends, and digital developments in their respective fields. Professionalism, tradition, standards, respected bodies of knowledge and individual practicing professionals' personality traits are closely examined over both volumes. Inside Major East Asian Library Collections in North America promotes shared understanding of librarians' work and contribution to society and will enable further collaborations and new services, utilizing the unique and distributed nature of their expertise.
Foreword / Ellen Hammond Foreword / Loretta E. Kim Foreword / Matthias Kaun Volume I: Japan and Korean Studies East Asian Librarianship and Library Collections in North America: Introduction -- Chapter 1. Kuniko yamada mcvey, librarian for the Japanese collection, harvard-yenching library, harvard university -- Chapter 2. Reiko yoshimura, head librarian freer gallery of arts and arthur m. Sackler gallery library, national museum of asian art, smithsonian libraries and archives -- Chapter 3. Dr. Kristina troost, head, east asian collection, duke university(retired) -- Chapter 4. Dr. daniel mckee, Japanese bibliographer, cornell university library -- Chapter 5. Yunah sung, korean studies librarian & project manager, asia library, university of michigan -- Chapter 6. Hyo jin moon, subject specialist for Japanese studies and korean studies, university of california san diego -- Chapter 7. Dr. Ann marie l. davis, associate professor, Japanese studies librarian, the ohio state university libraries -- Chapter 8. Dr. Steve witt, subject specialist librarian for global studies and Japanese studies and head of the international & area studies library, university of illinois at urbana-champaign -- Chapter 9. Adam lisbon, Japanese & korean studies librarian, university of colorado boulder -- Chapter 10. Dr. Rebecca corbett, Japanese studies librarian, university of southern california -- Chapter 11. Joy kim, curator, korean heritage library, university of southern california -- Chapter 12. Ellie kim, korea studies librarian, university of hawaii at manoa library -- Chapter 13. Tokiko bazzell, Japan studies librarian, university of hawaii at manoa -- Chapter 14. Kana jenkins, curator, gordon w. Prange collection, east asian studies librarian, university of maryland -- Chapter 15. Sharon domier, east asian studies librarian, university of massachusetts amherst -- Chapter 16. Dr. Beth sara katzoff, east asian studies librarian, new york university -- Chapter 17. Hana kim, director, cheng yu tung east asian library, university of toronto -- Chapter 18. Shirin eshghi, head, asian library, university of British columbia -- Chapter 19. Katherine kalsbeek, head, rare books & special collections / Saeyong Kim, Korean Studies Librarian / Tomoko Kitayama, Japanese Studies Librarian / Jing Liu, Chinese Studies Librarian / Sarbjit Randhawa, South Asian and Himalayan Studies Librarian, Asian Library, University of British Columbia -- Chapter 20. David sulz, public services librarian (includes east asian studies) -- Chapter 21. Dr. Max dionisio, acting department head, library and archives and the bishop white committee library of east asia, royalOntario museum -- Chapter 22. Cordes tarantino, assistant librarian, c. Laan chun library, asian art museum of san francisco -- Chapter 23. Dr. Hermina g.b. Anghelescu and alice yuet ling law, east asian librarianship and library collections in the United States and Canada: A selective bibliography, 2000-2020 east asian librarianship and library collections in North America: Conclusion.
Includes bibliographical references and index.
Keywords: Libraries -- United States -- Special collections -- East Asia; Libraries -- Canada -- Special collections -- East Asia; East Asian literature -- United States; East Asian literature -- Canada; Subject specialist librarians -- United States -- Interviews; Subject specialist librarians -- Canada -- Interviews; Literary collections / Asian -- General; Library & information sciences